Coupling of Single Molecule, Long Read Sequencing with IMGT/HighV-QUEST Analysis Expedites Identification of SIV gp140-Specific Antibodies from scFv Phage Display Libraries - Han, Seung Yub; Antoine, Alesia; Howard, David; Chang, Bryant; Chang, Woo Sung; Slein, Matthew; Deikus, Gintaras; Kossida, Sofia; Duroux, Patrice; Lefranc, Marie-Paule; Sebra, Robert P.; Smith, Melissa L.; et al. (Frontiers in Immunology, 2018)
The simian immunodeficiency virus (SIV)/macaque model of human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome pathogenesis is critical for furthering our understanding of the role of antibody responses in the prevention of HIV infection, and will only increase in importance as macaque immunoglobulin (IG) gene databases are expanded. We have previously reported the construction of a phage display library from a SIV-infected rhesus macaque (Macaca mulatta) using oligonucleotide primers based on human IG gene sequences. Our previous screening relied on Sanger sequencing, which was inefficient and generated only a few dozen sequences. Here, we re-analyzed this library using single molecule, real-time (SMRT) sequencing on the Pacific Biosciences (PacBio) platform to generate thousands of highly accurate circular consensus sequencing (CCS) reads corresponding to full length single chain fragment variable. CCS data were then analyzed through the international ImMunoGeneTics information system® (IMGT®)/HighV-QUEST (www.imgt.org) to identify variable genes and perform statistical analyses. Overall the library was very diverse, with 2,569 different IMGT clonotypes called for the 5,238 IGHV sequences assigned to an IMGT clonotype. Within the library, SIV-specific antibodies represented a relatively limited number of clones, with only 135 different IMGT clonotypes called from 4,594 IGHV-assigned sequences. Our data did confirm that the IGHV4 and IGHV3 gene usage was the most abundant within the rhesus antibodies screened, and that these genes were even more enriched among SIV gp140-specific antibodies. Although a broad range of VH CDR3 amino acid (AA) lengths was observed in the unpanned library, the vast majority of SIV gp140-specific antibodies demonstrated a more uniform VH CDR3 length (20 AA). This uniformity was far less apparent when VH CDR3 were classified according to their clonotype (range: 9–25 AA), which we believe is more relevant for specific antibody identification. Only 174 IGKV and 588 IGLV clonotypes were identified within the VL sequences associated with SIV gp140-specific VH. Together, these data strongly suggest that the combination of SMRT sequencing with the IMGT/HighV-QUEST querying tool will facilitate and expedite our understanding of polyclonal antibody responses during SIV infection and may serve to rapidly expand the known scope of macaque V genes utilized during these responses.